2021
DOI: 10.1007/s11051-021-05314-1
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles–chitosan composites activity against resistant bacteria: tolerance and biofilm inhibition

Abstract: This study aimed to evaluate the effectiveness of silver nanoparticles–chitosan composites (AgNPs) with different morphologies and particle size distributions against resistant bacteria and biofilm formation. Four different samples were prepared by a two-step procedure using sodium borohydride and ascorbic acid as reducing agents and characterized by UV–Vis absorption spectra, scanning transmission electron microscopy. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Santos et al [39], when analyzing the production of the EPS matrix by E. coli, K. pneumoniae, P. aeruginosa, and S. aureus strains through the Congo red method, noticed that after the incorporation of AgNPs into Congo red agar, there was no evident EPS matrix formation, as only red colonies with a mucous texture appeared on the Petri dishes. Therefore, these studies indicate that agents with bactericidal properties, when incorporated into Congo red agar, can reduce both bacterial load and the production of EPS matrix during biofilm formation, as was evidenced in our study, especially after VAN incorporation into HYDROGEL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Santos et al [39], when analyzing the production of the EPS matrix by E. coli, K. pneumoniae, P. aeruginosa, and S. aureus strains through the Congo red method, noticed that after the incorporation of AgNPs into Congo red agar, there was no evident EPS matrix formation, as only red colonies with a mucous texture appeared on the Petri dishes. Therefore, these studies indicate that agents with bactericidal properties, when incorporated into Congo red agar, can reduce both bacterial load and the production of EPS matrix during biofilm formation, as was evidenced in our study, especially after VAN incorporation into HYDROGEL.…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative determination of the inhibition of the slime production and the exopolysaccharide matrix production was carried out by the Congo red method according to Santos et al [39]. MRSA ATCC 33591 was adjusted in brain heart infusion broth (BHI) to 0.5 on the McFarland scale and incubated at 35 ± 2 • C for 24 h. An aliquot of bacterial growth was then seeded on Congo red agar petri dishes containing HYDROGEL at 0.25%, and VAN and VAN-HYDROGEL at 0.5 × MIC.…”
Section: Antibiofilm Activity Congo Red Agar Methodsmentioning
confidence: 99%
“…The results indicated that AgNPs could prevent biofilm formation, detach biofilm cells, and increase the susceptibility of biofilm cells to antibiotics. A study by [ 89 ] synthesized AgNPs–chitosan composites and assessed their antibiofilm activity against multi-drug-resistant Acinetobacter baumannii . The results suggested that the AgNPs–chitosan composites could inhibit biofilm formation, disrupt biofilm structure, reduce biofilm biomass, and enhance the activity of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Many alternatives to antibiotics have been investigated to fight against P. aeruginosa. Use of antibacterial nanoparticles is considered to be a promising nonconventional therapy for fighting antibiotic-resistant bacteria owing to its excellent antibacterial activity. …”
Section: Introductionmentioning
confidence: 99%